2011
DOI: 10.1158/1078-0432.ccr-10-3099
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deprivation Suppresses Hepatocellular Carcinoma Growth in Experimental Studies

Abstract: Purpose: Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death, and iron overload is a significant risk factor in the development of HCC. In this study, we investigated the potential application of depriving iron by a novel iron chelator, thiosemicarbazone-24 (TSC24), in HCC treatment.Experimental Design: Two HCC cell lines and HFE knockout (HFE À/À ) mice were used to determine iron chelation efficiency of TSC24. The anticancer effects of TSC24 on HCC were analyzed in vitro and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 42 publications
(51 reference statements)
1
55
1
Order By: Relevance
“…These inhibitory effects of DFO and DFX on L1210 leukemia cells were closely related to apoptosis, because the effects of DFO and DFX on viability of L1210 leukemia cells showed a similar trend to that of the apoptosis-inducing activity of DFO and DFX on L1210 leukemia cells. In this study, the apoptotic effects of DFO and DFX on L1210 leukemia cells agree with the results of other studies indicating that ICAs induce apoptosis in rapid proliferating cells such as myeloid leukemia cells, and hepatoma cells [9][10][11][12]. Our study showed that the ICA-mediated apoptosis of L1210 leukemia cells was not associated with the Fas/FasL pathway.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These inhibitory effects of DFO and DFX on L1210 leukemia cells were closely related to apoptosis, because the effects of DFO and DFX on viability of L1210 leukemia cells showed a similar trend to that of the apoptosis-inducing activity of DFO and DFX on L1210 leukemia cells. In this study, the apoptotic effects of DFO and DFX on L1210 leukemia cells agree with the results of other studies indicating that ICAs induce apoptosis in rapid proliferating cells such as myeloid leukemia cells, and hepatoma cells [9][10][11][12]. Our study showed that the ICA-mediated apoptosis of L1210 leukemia cells was not associated with the Fas/FasL pathway.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that iron supplementation can partially or completely reverse the inhibitory effects of ICAs on various cells [5,6,9,10]. Ferric iron was reported to be less effective in restoring the viability of tumor cells than ferrous iron [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37][38][39][40] Here, we present results of the rst systematically organized investigation of antitumor activity of three mono-carbohydrazones and three mono-thiocarbohydrazones with their corresponding bisstructural counterparts. Despite the development of new therapeutics with increasing success in treating malignancies, recurrence of disease can develop years aer efficient therapy.…”
mentioning
confidence: 99%